Anti-corrosion nano black passivation type metal material as well as preparation process and application thereof

Anti-corrosion and nano-black passivation metal materials prepared through powder metallurgy process solve the problems of low salt spray resistance and complex process of existing galvanized steels, achieving high salt spray resistance and good accuracy, and improving product quality and reduce costs.

CN119464890AActive Publication Date: 2025-02-18KUNSHAN FUWEI METAL PROD CO LTD

Patent Information

Application Number
CN202411616080.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2025-02-18
Estimated Expiration
2044-11-13

AI Technical Summary

Technical Problem

The salt spray resistance of existing galvanized steel is lower than that of the electronics industry, and the galvanizing process is complex, which affects the accuracy of electronic devices, resulting in a decrease in product yield and an increase in cost.

Method used

The anti-corrosion, nano-black passivation metal material is prepared by powder metallurgy technology. The material consists of stainless steel powder, surface modified tungsten carbide and spherical graphene modified stainless steel powder, and is formed by thermal isostatic pressure and high-energy laser melting treatment. Nanopassivation coating.

Benefits of technology

This material meets the requirements of the electronics industry for the salt spray resistance of steel, without subsequent electroplating treatment, improves the accuracy of electronic devices, improves product yield and reduces production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention relates to the technical field of alloy materials, in particular to an anti-corrosion nano black passivation type metal material and a preparation technology and application thereof. The invention discloses an anti-corrosion nano black passivation type metal material which is prepared from stainless steel powder, tungsten carbide subjected to surface modification treatment and spherical graphene modified stainless steel powder through a powder metallurgy process. The total mass of the tungsten carbide subjected to surface modification treatment and the spherical graphene modified stainless steel powder is 0.5-1.0 wt% of the mass of the anti-corrosion nano black passivation type metal material; the mass ratio of the tungsten carbide subjected to surface modification treatment to the spherical graphene modified stainless steel powder is 1: (0.1-5); the tungsten carbide subjected to surface modification treatment comprises matrix tungsten carbide and nano modified metal particles loaded on the surface of the matrix tungsten carbide. The anti-corrosion nano black passivation type metal material meets the salt spray resistance of steel in the electronic industry, subsequent electroplating treatment is not needed, the precision of electronic devices is relatively good, the product yield is improved, and the product cost is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of alloy materials, and in particular to an anti-corrosion, nano-black passivation type metal material and its preparation process and application. Background Art

[0002] At present, in order to prevent steel from being corroded by the external environment and extend the overall service life of steel, the surface of steel is treated with anti-corrosion. The most popular anti-corrosion treatment method is to electroplating a zinc layer on the surface of steel. Galvanized steel has good corrosion resistance and is widely used in electronic devices, home appliances, vehicles and ships, mechanical parts and other fields.

[0003] According to GB / T 2518-2008, the salt spray resistance test for galvanized steel is 72H±1H. Different galvanizing processes and the thickness and uniformity of the galvanized layer will affect the salt spray resistance of galvanized steel. The salt spray resistance of existing galvanized steel is lower than 73H, while the salt spray resistance of steel in the electronics industry is ≥76H, resulting in the inability of existing galvanized steel to meet the high salt spray resistance requirements of the electronics industry for electronic devices. In addition, electronic devices in the electronics industry are of high precision and difficult to process. The use of galvanizing technology to treat the surface of steel is not only relatively complicated, but also affects the precision of electronic devices, resulting in a decrease in product yield and an invisible increase in product costs.

[0004] In view of the technical difficulties existing in the above-mentioned prior art, the inventor provides an anti-corrosion, nano-black passivation type metal material and its preparation process and application. Summary of the invention

[0005] In order to solve the problem that the above-mentioned prior art has deviation in salt spray resistance, cannot meet the high salt spray resistance requirements of the electronics industry for electronic devices, and the process is relatively complicated and affects the precision of electronic devices, resulting in a decrease in product yield and an invisible increase in product costs, the present application provides an anti-corrosion, nano-black passivated metal material and its preparation process and application, which can meet the salt spray resistance requirements of steel in the electronics industry and do not require subsequent electroplating treatment. The precision of electronic devices is relatively good, the product yield is improved, and the product cost is reduced.

[0006] The present application provides an anti-corrosion, nano-black passivation type metal material, which is achieved through the following scheme:

[0007] A corrosion-resistant, nanometer black passivation metal material is made of stainless steel powder, surface-modified tungsten carbide and spherical graphene-modified stainless steel powder through a powder metallurgy process; the total mass of the surface-modified tungsten carbide and the spherical graphene-modified stainless steel powder is equal to 0.5-1.0wt% of the mass of the corrosion-resistant, nanometer black passivation metal material; the mass ratio of the surface-modified tungsten carbide to the spherical graphene-modified stainless steel powder is 1:(0.1-5); the surface-modified tungsten carbide comprises a matrix tungsten carbide and nanometer-modified metal particles loaded on the surface of the matrix tungsten carbide, and the nanometer-modified metal particles at least comprise nanometer iron particles.

[0008] The anti-corrosion, nano-black passivated metal material of the present invention meets the salt spray resistance of steel in the electronics industry and does not require subsequent electroplating treatment. The precision of electronic devices is relatively good, the product yield is improved, and the product cost is reduced.

[0009] Preferably, the matrix tungsten carbide is nano tungsten carbide with an average particle size of 50-500 nm; the nano modified metal particles are loaded on the surface of the matrix tungsten carbide by a sol-gel method, and the loading rate of the nano modified metal particles is ≥5wt%.

[0010] By adopting the above technical solution, the compatibility of nano tungsten carbide and the iron matrix is ​​improved, so that the surface-modified tungsten carbide is evenly dispersed inside the iron matrix, thereby improving the overall corrosion resistance and wear resistance.

[0011] Preferably, the spherical graphene modified stainless steel powder is made of stainless steel powder and surface modified graphene by a spray method; the added amount of the surface modified graphene is equal to 5-10wt% of the mass of the spherical graphene modified stainless steel powder; the particle size D50 of the spherical graphene modified stainless steel powder is ≤35 microns.

[0012] Preferably, the surface-modified graphene comprises a matrix graphene and nano-modified metal particles loaded on the surface of the matrix graphene, and the loading rate of the nano-modified metal particles is ≥5wt%; the nano-modified metal particles at least comprise nano-iron particles.

[0013] Preferably, the surface-modified graphene includes matrix graphene and metal single atoms anchored at defect sites of the matrix graphene, the metal single atom loading rate is ≥1wt%, and the metal single atoms include at least iron single atoms.

[0014] By adopting the above technical solution, the compatibility of the matrix graphene and the iron matrix is ​​improved, which facilitates the uniform dispersion of the surface-modified graphene inside the iron matrix, thereby improving the overall corrosion resistance, wear resistance and mechanical strength.

[0015] Preferably, the preparation method of the spherical graphene modified stainless steel powder is as follows:

[0016] S1. The stainless steel powder and the surface-modified graphene were mixed evenly and then transferred to a planetary ball mill, and tungsten carbide was used as grinding beads, and dry ball milling was performed at 60-80 rpm for 20-40 min to obtain a mixed alloy powder;

[0017] S2. The mixed alloy powder obtained in S1 is used to prepare spherical alloy powder by aerosol method. The particle size of the obtained spherical alloy powder is D 50 5-35 microns, tap density ≥1.75g / cm 3 .

[0018] By adopting the above technical scheme, the prepared spherical graphene modified stainless steel powder has good dispersion performance with stainless steel powder, which can improve the dispersion uniformity of the spherical graphene modified stainless steel powder in the iron matrix, thereby improving the overall corrosion resistance, wear resistance and mechanical strength.

[0019] Preferably, the total mass of the surface-modified tungsten carbide and the spherical graphene-modified stainless steel powder is equal to 0.7-0.8wt% of the mass of the anti-corrosion, nano-black passivation type metal material; the mass ratio of the surface-modified tungsten carbide to the spherical graphene-modified stainless steel powder is 1:(0.5-2).

[0020] Preferably, the total mass of the surface-modified tungsten carbide and the spherical graphene-modified stainless steel powder is equal to 0.7-0.8wt% of the mass of the anti-corrosion, nano-black passivation type metal material; the mass ratio of the surface-modified tungsten carbide to the spherical graphene-modified stainless steel powder is 3:2.

[0021] By adopting the above technical solution, the salt spray resistance performance of steel materials required by the electronics industry can be met while reducing the overall production cost.

[0022] The present application provides a preparation process for an anti-corrosion, nano-black passivation type metal material, which is achieved by the following scheme:

[0023] A preparation process of an anti-corrosion, nano-black passivation type metal material comprises the following steps:

[0024] Step 1, preparation of surface-modified tungsten carbide and spherical graphene-modified stainless steel powder;

[0025] Step 2: The surface-modified tungsten carbide and spherical graphene-modified stainless steel powder prepared in step 1 are mixed evenly with the stainless steel powder according to a ratio, and then transferred to a planetary ball mill, with tungsten carbide as a grinding bead, and dry-milled at 60-80 rpm for 5-15 minutes to obtain a mixed alloy powder;

[0026] Step 3: The mixed alloy powder obtained in step 2 is placed in a molding die for hot isostatic pressing. The hot isostatic pressing parameters are as follows: molding temperature 880-950°C, molding pressure: first pressurize to 120-160MPa at 15-20MPa / s, hold pressure for 10-20s, then pressurize to 200-240MPa at 8-10MPa / s, hold pressure for 20-30s, then pressurize to 320-350MPa at 4-6MPa / s, hold pressure for 20-30s, and then pressurize to 4 at 1-2MPa / s. 50-500MPa, hold pressure for 30-60s, then pressurize to 550-600MPa at 0.5-1MPa / s, hold pressure for 30-60s, then reduce pressure to 280-320MPa at 1-2MPa / s, hold pressure for 30-60s, then reduce pressure to 160-200MPa at 4-8MPa / s, hold pressure for 30-60s, finally reduce pressure to 0MPa at 15-20MPa / s, molding speed is 0.5-5mm / s, cool to room temperature, grind burrs to get semi-finished products;

[0027] Step 4: Perform high-energy laser melting treatment on the surface of the semi-finished product obtained in step 3, with a laser spot temperature of 2880-3000°C, a laser scanning speed of 400-1200mm / s, and a spot diameter of 0.04-0.08mm. After the high-energy laser melting treatment, perform quenching + tempering treatment to obtain an anti-corrosion metal material, and apply a nano passivation coating of 8-20μm thickness on the anti-corrosion metal material by roller coating, and bake at 150-250°C until completely dry to obtain a finished anti-corrosion, nano black passivation metal material;

[0028] The nano passivation coating is made of nano passivation paint, which includes water-based polyester resin, silane coupling agent, carbon black, and black titanium dioxide nanoparticles. The total mass of carbon black and black titanium dioxide nanoparticles accounts for 3-10wt% of the total mass of the nano passivation paint; the mass of the silane coupling agent accounts for 0.5-1.0wt% of the total mass of the nano passivation paint; the solid content of the water-based polyester resin is 30-55wt%, and the mass of the polyurethane latex particles in the nano passivation paint accounts for 25-40wt% of the total mass of the nano passivation paint.

[0029] In the preparation process of the present invention, a high-energy laser is used to perform melting treatment on the surface of the steel material, thereby improving the compatibility of the surface-modified tungsten carbide with the stainless steel matrix, which is beneficial to improving the overall corrosion resistance of the steel material.

[0030] The preparation process of the invention is relatively simple, has low operation difficulty, and is easy to realize industrial production and manufacturing.

[0031] An anti-corrosion, nano-black passivated metal material is used for internal metal parts of electronic products.

[0032] In summary, this application has the following advantages:

[0033] 1. The anti-corrosion, nano-black passivated metal material of the present invention is applied to the internal metal parts of electronic products, which can meet the salt spray resistance of steel in the electronics industry without the need for subsequent electroplating treatment. The precision of electronic devices is relatively good, the product yield is improved, and the product cost is reduced.

[0034] 2. The preparation process of the present application is relatively simple, with low operating difficulty, and is easy to implement industrial production. DETAILED DESCRIPTION

[0035] In order to further understand the present invention, preferred embodiments of the present invention are described below in conjunction with examples and comparative examples.

[0036] Example

[0037] The invention discloses an anti-corrosion nano black passivation type metal material which is made of stainless steel powder, surface-modified tungsten carbide and spherical graphene-modified stainless steel powder through a powder metallurgy process.

[0038] The total mass of the surface-modified tungsten carbide and spherical graphene-modified stainless steel powder is equal to 0.5-1.0wt% of the mass of the anti-corrosion, nano-black passivation type metal material.

[0039] Preferably, the total mass of the surface-modified tungsten carbide and the spherical graphene-modified stainless steel powder is equal to 0.7-0.8wt% of the mass of the anti-corrosion, nano-black passivation type metal material.

[0040] The mass ratio of the surface-modified tungsten carbide to the spherical graphene-modified stainless steel powder is 1:(0.1-5).

[0041] Preferably, the mass ratio of the surface-modified tungsten carbide to the spherical graphene-modified stainless steel powder is 1:(0.5-2).

[0042] The surface-modified tungsten carbide comprises a substrate tungsten carbide and nano-modified metal particles loaded on the surface of the substrate tungsten carbide, wherein the nano-modified metal particles at least comprise nano-iron particles. The substrate tungsten carbide is nano-tungsten carbide with an average particle size of 50-500nm. The nano-modified metal particles are loaded on the surface of the substrate tungsten carbide by a sol-gel method, and the loading rate of the nano-modified metal particles is ≥5wt%.

[0043] The spherical graphene-modified stainless steel powder is prepared from stainless steel powder and surface-modified graphene by a spraying method.

[0044] The added amount of the surface modified graphene is equal to 5-10wt% of the mass of the spherical graphene modified stainless steel powder.

[0045] The particle size of spherical graphene modified stainless steel powder is D50≤35 microns.

[0046] The surface modified graphene includes a matrix graphene and nano-modified metal particles loaded on the surface of the matrix graphene, wherein the loading rate of the nano-modified metal particles is ≥5wt%. The nano-modified metal particles at least include nano-iron particles. Alternatively, the surface modified graphene includes a matrix graphene and metal single atoms anchored at defective points of the matrix graphene, wherein the loading rate of the metal single atoms is ≥1wt%, and the metal single atoms at least include iron single atoms.

[0047] The preparation method of spherical graphene modified stainless steel powder is as follows:

[0048] S1. The stainless steel powder and the surface-modified graphene were mixed evenly and then transferred to a planetary ball mill, and tungsten carbide was used as grinding beads, and dry ball milling was performed at 60-80 rpm for 20-40 min to obtain a mixed alloy powder;

[0049] S2. The mixed alloy powder obtained in S1 is used to prepare spherical alloy powder by aerosol method. The particle size of the obtained spherical alloy powder is D 50 5-35 microns, tap density ≥1.75g / cm 3 .

[0050] A preparation process of an anti-corrosion, nano-black passivation type metal material comprises the following steps:

[0051] Step 1, preparation of surface-modified tungsten carbide and spherical graphene-modified stainless steel powder;

[0052] Step 2: The surface-modified tungsten carbide and spherical graphene-modified stainless steel powder prepared in step 1 are mixed evenly with the stainless steel powder according to a ratio, and then transferred to a planetary ball mill, with tungsten carbide as a grinding bead, and dry-milled at 60-80 rpm for 5-15 minutes to obtain a mixed alloy powder;

[0053] Step 3: The mixed alloy powder obtained in step 2 is placed in a molding die for hot isostatic pressing. The hot isostatic pressing parameters are as follows: molding temperature 880-950°C, molding pressure: first pressurize to 120-160MPa at 15-20MPa / s, hold pressure for 10-20s, then pressurize to 200-240MPa at 8-10MPa / s, hold pressure for 20-30s, then pressurize to 320-350MPa at 4-6MPa / s, hold pressure for 20-30s, and then pressurize to 4 at 1-2MPa / s. 50-500MPa, hold pressure for 30-60s, then pressurize to 550-600MPa at 0.5-1MPa / s, hold pressure for 30-60s, then reduce pressure to 280-320MPa at 1-2MPa / s, hold pressure for 30-60s, then reduce pressure to 160-200MPa at 4-8MPa / s, hold pressure for 30-60s, finally reduce pressure to 0MPa at 15-20MPa / s, molding speed is 0.5-5mm / s, cool to room temperature, grind burrs to get semi-finished products;

[0054] Step 4: Perform high-energy laser melting treatment on the surface of the semi-finished product obtained in step 3, with a laser spot temperature of 2880-3000°C, a laser scanning speed of 400-1200mm / s, and a spot diameter of 0.04-0.08mm. After the high-energy laser melting treatment, quenching + tempering treatment is performed to obtain an anti-corrosion metal material. The anti-corrosion metal material is coated with a 8-20μm thick nano-passivation coating by roller coating, and baked at 150-250°C until completely dry to obtain a finished anti-corrosion, nano-black passivation metal material.

[0055] The nano passivation coating is made of nano passivation paint, which includes water-based polyester resin, silane coupling agent, carbon black, and black titanium dioxide nanoparticles.

[0056] The total mass of carbon black and black titanium dioxide nanoparticles accounts for 3-10wt% of the total mass of the nano passivation coating.

[0057] The mass ratio of carbon black to black titanium dioxide nanoparticles is 1:(0.2-0.4).

[0058] The mass of the silane coupling agent accounts for 0.5-1.0wt% of the total mass of the nano passivation coating. Preferably, the silane coupling agent is KH570, and the mass of KH570 accounts for 0.6-0.75wt% of the total mass of the nano passivation coating.

[0059] The solid content of the waterborne polyester resin is 30-55wt%, and the mass of the polyurethane latex particles in the nano passivation coating accounts for 25-40wt% of the total mass of the nano passivation coating.

[0060] The anti-corrosion, nano-black passivation type metal material of the present invention is applied to the internal metal parts of electronic products, which can meet the salt spray resistance performance of steel in the electronics industry (GB / T 2518-2008 salt spray resistance test 78H-85H) and does not require subsequent electroplating treatment. The precision of electronic devices is relatively good, and the product yield of the anti-corrosion, nano-black passivation type metal material is improved, the product production cost is reduced, and the production competitive advantage is enhanced.

[0061] Preparation Example 1: Surface-modified tungsten carbide is prepared by a sol-gel method. The preparation method is as follows:

[0062] S1. Add 4.04 g of ferric nitrate nonahydrate (Fe(NO3)3·9H2O, molecular weight 404, iron content 13.82 wt%), 250 mL of distilled water, and a magnetic stirrer into a 500 mL beaker, adjust the magnetic speed to 160 rpm and stir for 30 min to obtain an aqueous solution of ferric nitrate with a concentration of 0.04 mol / L;

[0063] S2. At a stirring speed of 160rpm, 20g of nano-tungsten carbide (Brofos-WC-200 nano-tungsten carbide purchased by Bohuas Nano Technology (Ningbo) Co., Ltd., with an average particle size of 200nm, a purity of 99.9%, and a hexagonal crystal) was added to a 500mL beaker. The addition rate of nano-tungsten carbide was 0.2g / s. After the addition of nano-tungsten carbide, magnetic stirring was maintained at 160rpm for 5min, and the magnetic stirring bar was taken out. Ultrasonic stirring was performed using an ultrasonic stirrer with an ultrasonic frequency of 44kHz and a power of 600W. After ultrasonic dispersion was performed for 30min, a water bath was heated to 45°C, and a 3.2wt% ammonia solution was added. The ammonia solution was dropped at an acceleration of 2 drops / s and dripped onto the Fe 3+ After complete precipitation, Fe(OH)3 was formed, and a magnetic stirring bar was placed, and magnetic stirring was performed at 80 rpm for 2 h, and then the Fe(OH)3 / WC binary colloid was obtained after aging for 24 h.

[0064] S3. After washing the Fe(OH)3 / WC binary colloid three times with distilled water, the Fe(OH)3 / BN solid material was obtained by filtration under reduced pressure and vacuum drying and set aside;

[0065] S4. The obtained Fe(OH)3 / BN solid material was transferred to an atmosphere tube furnace for calcination treatment, and the temperature was raised to 800°C at 10°C / min in an air atmosphere and calcined for 5.0h to obtain Fe2O3@WC composite powder, and then a hydrogen-argon mixture was introduced into the atmosphere tube furnace, wherein the volume ratio of hydrogen to argon in the hydrogen-argon mixture was 1:4, and a reduction reaction was carried out at 800°C for 6.0h. After the reduction reaction was completed, the furnace was opened and naturally cooled to room temperature to obtain nano-Fe@WC solid powder;

[0066] S5. The obtained nano-Fe@WC solid powder was placed in a planetary ball mill and nitrogen was introduced for protection. In the nitrogen atmosphere, low-speed ball milling was performed using tungsten carbide as grinding beads. The tungsten carbide with surface nano-Fe modified was obtained by ball milling at 60 rpm for 30 min. The nano-Fe loading rate was 2.99 wt%.

[0067] The difference between Preparation Example 2 and Preparation Example 1 is: S1. 6.9 g of ferric nitrate nonahydrate, 250 mL of distilled water, and a magnetic stirrer are added to a 500 mL beaker, and the magnetic speed is adjusted to 160 rpm and stirred for 30 min to obtain an aqueous solution of ferric nitrate with a concentration of 0.0684 mol / L. The nano-Fe loading rate in the obtained tungsten carbide with surface nano-Fe modification is 5.01 wt%.

[0068] The difference between Preparation Example 3 and Preparation Example 1 is: S1. 14.3g of ferric nitrate nonahydrate, 250mL of distilled water, and a magnetic stirrer are added to a 500mL beaker, and the magnetic speed is adjusted to 160rpm and stirred for 30min to obtain an aqueous solution of ferric nitrate with a concentration of 0.142mol / L. The nano-Fe loading rate in the obtained tungsten carbide with surface nano-Fe modified treatment is 9.90wt%.

[0069] Preparation Example 4 is different from Preparation Example 1 in that: S1. 30.3 g of ferric nitrate nonahydrate, 250 mL of distilled water, and a magnetic stirrer are added to a 500 mL beaker, and the magnetic speed is adjusted to 160 rpm and stirred for 30 min to obtain an aqueous solution of ferric nitrate with a concentration of 0.3 mol / L. The nano-Fe loading rate in the obtained tungsten carbide with surface nano-Fe modification is 19.04 wt%.

[0070] Preparation Example 5: Surface modified graphene is prepared by a sol-gel method, and the preparation method is as follows:

[0071] S1. Add 0.404 g of ferric nitrate nonahydrate, 250 mL of distilled water, and a magnetic stirrer into a 500 mL beaker, adjust the magnetic speed to 160 rpm and stir for 30 min to obtain an aqueous solution of ferric nitrate with a concentration of 0.004 mol / L;

[0072] S2. At a stirring speed of 320 rpm, 2 g of amino graphene (amino graphene BKMK2009, purity 98%, thickness 0.55-3.74 nm, size 0.5-3 μm, number of layers 10, ordered by Suzhou Kaifa New Materials Technology Co., Ltd.) was added to a 500 mL beaker. The addition rate of amino graphene was 0.1 g / s. After the addition of nano-tungsten carbide, magnetic stirring was maintained at 320 rpm for 5 min. The magnetic stirring bar was removed and ultrasonic stirring was performed using an ultrasonic stirrer with an ultrasonic frequency of 44 kHz and a power of 600 W. After ultrasonic dispersion was performed for 30 min, the water bath was heated to 50 ° C and ammonia water with a concentration of 3.2 wt% was added. The ammonia water droplet acceleration was 1 drop / s and dripped onto the Fe 3+ After complete precipitation, Fe(OH)3 was formed, and a magnetic stirring bar was placed in the mixture, and magnetic stirring was performed at 200 rpm for 2 h. After aging for 24 h, Fe(OH)3 / AGS binary colloid was obtained.

[0073] S3. After washing the Fe(OH)3 / AGS binary colloid three times with distilled water, the Fe(OH)3 / AGS solid material was obtained by filtration under reduced pressure and vacuum drying for standby use;

[0074] S4. The obtained Fe(OH)3 / BN solid material was transferred to an atmosphere tube furnace for calcination treatment, and the temperature was raised to 760°C at 10°C / min in an air atmosphere for calcination for 4 hours to obtain Fe2O3@WC composite powder, and then a hydrogen-argon mixture was introduced into the atmosphere tube furnace, wherein the volume ratio of hydrogen to argon in the hydrogen-argon mixture was 1:3, and a reduction reaction was carried out at 760°C for 4.0 hours. After the reduction reaction was completed, the furnace was opened and naturally cooled to room temperature to obtain nano-Fe@AGS solid powder;

[0075] S5. The obtained nano-Fe@AGS solid powder was placed in a planetary ball mill and nitrogen was introduced for protection. In the nitrogen atmosphere, low-speed ball milling was performed using tungsten carbide as grinding beads. The graphene with surface nano-Fe modified was obtained by ball milling at 60 rpm for 60 min. The nano-Fe loading rate was 2.98 wt%.

[0076] Preparation Example 6 is different from Preparation Example 5 in that: S1. 6.95 g of ferric nitrate nonahydrate, 250 mL of distilled water, and a magnetic stirrer are added to a 500 mL beaker, and the magnetic speed is adjusted to 160 rpm and stirred for 30 min to obtain an aqueous solution of ferric nitrate with a concentration of 0.0684 mol / L. The nano-Fe loading rate in the obtained graphene with surface nano-Fe modification is 5.03 wt%.

[0077] Preparation Example 7 is different from Preparation Example 5 in that: S1. 14.3 g of ferric nitrate nonahydrate, 250 mL of distilled water, and a magnetic stirrer are added to a 500 mL beaker, and the magnetic speed is adjusted to 160 rpm and stirred for 30 min to obtain an aqueous solution of ferric nitrate with a concentration of 0.142 mol / L. The nano-Fe loading rate in the obtained graphene with surface nano-Fe modification is 9.85 wt%.

[0078] Preparation Example 8 is different from Preparation Example 5 in that: S1. 30.3 g of ferric nitrate nonahydrate, 250 mL of distilled water, and a magnetic stirrer are added to a 500 mL beaker, and the magnetic speed is adjusted to 160 rpm and stirred for 30 min to obtain an aqueous solution of ferric nitrate with a concentration of 0.3 mol / L. The nano-Fe loading rate in the obtained graphene with surface nano-Fe modification is 19.01 wt%.

[0079] Preparation Example 9: The surface-modified graphene is metal single-atom Fe-modified graphene (produced by Beijing Graphene Technology Research Institute Co., Ltd.), and the preparation method is as follows:

[0080] S1. 2 g of graphene (graphene TNRGO from Chengdu Organic Chemistry Co., Ltd., Chinese Academy of Sciences, with a specific surface area of ​​500-1000 m2 / g, a thickness of 0.55-3.74 nm, a diameter of 0.5-3 μm, and a number of layers of <10) was dispersed in 500 g of distilled water to obtain a graphene dispersion;

[0081] At the same time, dissolve 2g of KOH in 250mL of distilled water and mix well to obtain 8g / L KOH aqueous solution;

[0082] S2. Add the graphene dispersion in S1 and the 8g / L KOH aqueous solution in S1 into a 1.5L beaker and stir magnetically at 200rpm for 15min. After mixing evenly, heat the water bath to 80℃, stir and mix at 200rpm for 10min at 80℃, remove the magnetic stirrer, and use an ultrasonic stirrer for ultrasonic stirring. The ultrasonic frequency is 44kHz and the power is 600W. The ultrasonic dispersion is carried out for 30min, and the pressure is reduced. Vacuum drying can obtain the graphene with surface alkali treatment;

[0083] S3. Put the obtained surface alkali-treated graphene into crucible A, put 0.12 g of ferric chloride into crucible B, load crucible A into the downstream area of ​​the tube furnace, load crucible B into the upstream area of ​​the tube furnace, seal the tube furnace, and in an argon atmosphere, raise the temperature of the upstream zone of the tube furnace from room temperature to 800° C. at a heating rate of 10° C. / min and keep it warm for 60 min. At the same time, raise the temperature of the downstream zone of the tube furnace from room temperature to 800° C. at a heating rate of 10° C. / min and keep it warm for 60 min to obtain a metal single atom-doped graphene precursor;

[0084] S4. Add the metal single atom doped graphene precursor into dilute hydrochloric acid at a concentration of 1.0 mol / L, stir, vacuum filter, wash with distilled water, and dry to obtain metal single atom Fe modified graphene, wherein the metal single atom Fe loading rate in the metal single atom Fe modified graphene is 0.49 wt%.

[0085] The difference between Preparation Example 10 and Preparation Example 9 is: S3. The obtained surface alkali-treated graphene is placed in crucible A, 0.28g of ferric chloride is placed in crucible B, crucible A is loaded in the downstream area of ​​the tube furnace, crucible B is loaded in the upstream area of ​​the tube furnace, the tube furnace is sealed, and in an argon atmosphere, the upstream temperature zone of the tube furnace is heated from room temperature to 800°C at a heating rate of 10°C / min for 60min, and the downstream temperature zone of the tube furnace is heated from room temperature to 800°C at a heating rate of 10°C / min for 60min, and a metal single atom doped graphene precursor is obtained. The metal single atom Fe loading rate in the obtained metal single atom Fe modified graphene is 1.01wt%.

[0086] The difference between Preparation Example 11 and Preparation Example 9 is: S3. The obtained surface alkali-treated graphene is placed in crucible A, 0.58g of ferric chloride is placed in crucible B, crucible A is loaded in the downstream area of ​​the tube furnace, crucible B is loaded in the upstream area of ​​the tube furnace, the tube furnace is sealed, and in an argon atmosphere, the upstream temperature zone of the tube furnace is heated from room temperature to 800°C at a heating rate of 10°C / min and kept warm for 60min, while the downstream temperature zone of the tube furnace is heated from room temperature to 800°C at a heating rate of 10°C / min and kept warm for 60min, to obtain a metal single atom doped graphene precursor. The metal single atom Fe loading rate in the obtained metal single atom Fe modified graphene is 1.98wt%.

[0087] The difference between Preparation Example 12 and Preparation Example 9 is: S3. The obtained surface alkali-treated graphene is placed in crucible A, 1.6g of ferric chloride is placed in crucible B, crucible A is loaded in the downstream area of ​​the tube furnace, crucible B is loaded in the upstream area of ​​the tube furnace, the tube furnace is sealed, and in an argon atmosphere, the upstream temperature zone of the tube furnace is heated from room temperature to 800°C at a heating rate of 10°C / min for 60min, and the downstream temperature zone of the tube furnace is heated from room temperature to 800°C at a heating rate of 10°C / min for 60min, and a metal single atom doped graphene precursor is obtained. The metal single atom Fe loading rate in the obtained metal single atom Fe modified graphene is 5.08wt%.

[0088] Example 1: An anti-corrosion, nano-black passivation type metal material is prepared by powder metallurgy process from stainless steel powder, surface-modified tungsten carbide in Preparation Example 2, and spherical graphene-modified stainless steel powder in Preparation Example 6. The total mass of the surface-modified tungsten carbide and spherical graphene-modified stainless steel powder is equal to 0.5wt% of the mass of the anti-corrosion, nano-black passivation type metal material. The mass ratio of the surface-modified tungsten carbide to the spherical graphene-modified stainless steel powder is 4:1.

[0089] A preparation process of an anti-corrosion, nano-black passivation type metal material comprises the following steps:

[0090] Step 1: The preparation method of surface-modified tungsten carbide is as described in Preparation Example 2;

[0091] The preparation method of spherical graphene modified stainless steel powder is shown in Preparation Example 6;

[0092] Step 2: The surface-modified tungsten carbide in Preparation Example 2 and the spherical graphene-modified stainless steel powder in Preparation Example 6 are mixed evenly with stainless steel powder (304 stainless steel powder from Hebei Ruihuang Metal Materials Co., Ltd., purity 99.9%, 500 mesh) according to a ratio, and then transferred to a planetary ball mill, with tungsten carbide as grinding beads, and dry ball milled at 80 rpm for 15 minutes to obtain a mixed alloy powder;

[0093] Step three, the mixed alloy powder obtained in step two is placed in a molding mold for hot isostatic pressing treatment, and the hot isostatic pressing parameters are as follows: molding temperature 920°C, molding pressure: first pressurize to 150MPa at 15MPa / s, hold pressure for 20s, then pressurize to 240MPa at 10MPa / s, hold pressure for 30s, then pressurize to 350MPa at 5MPa / s, hold pressure for 30s, then pressurize to 500MPa at 2MPa / s, hold pressure for 60s, then pressurize to 600MPa at 0.5MPa / s, hold pressure for 30s, then reduce the pressure to 300MPa at 2MPa / s, hold pressure for 60s, then reduce the pressure to 200MPa at 4MPa / s, hold pressure for 30s, and finally reduce the pressure to 0MPa at 20MPa / s, the molding speed is 1.0mm / s, cool to room temperature, and grind burrs to obtain a semi-finished product;

[0094] Step 4: Perform high-energy laser melting treatment on the surface of the semi-finished product obtained in step 3, with a laser spot temperature of 2950±5°C, a laser power of 420W, a laser scanning speed of 800mm / s, and a spot diameter of 0.08mm. After the high-energy laser melting treatment, cool it to room temperature and perform quenching treatment. Raise the temperature to 460°C at 5°C / min and keep it warm for 15min, adjust the temperature to 1020°C at 10°C / min, keep it warm for 90min, and then use gas quenching: input nitrogen and oxygen mixed gas with a temperature of 65°C, the oxygen volume content in the nitrogen and oxygen mixed gas is 15%, and fast Rapidly cool down to 400℃, and then carry out tempering treatment: adjust the temperature to 650℃ at 5℃ / min, keep warm for 1.5h, and then cool down to 220℃ at 10℃ / min, open the furnace and cool naturally, secondary tempering treatment: adjust the temperature to 680℃ at 6℃ / min, keep warm for 1.5h, and then cool down to 200℃ at 15℃ / min, open the furnace and cool naturally to room temperature to obtain anti-corrosion metal material, the anti-corrosion metal material is coated with 20μm thick nano passivation coating by roller coating, and baked at 175℃ until dry to obtain the finished anti-corrosion, nano black passivation metal material.

[0095] The nano-passivation coating is made of nano-passivation paint, which is made of 954g of water-based polyester resin (solid content is 32wt%, Refober R HYR-2402 water-based polyurethane resin, viscosity is 600mPa*s at 23°C, pH value is 7.7), 6g of silane coupling agent KH570, 30g of carbon black (carbon black TS720, Cabot), and 10g of black titanium dioxide nanoparticles (rutaceous 5nm titanium dioxide, Yamei Nano).

[0096] The difference between Example 2 and Example 1 is that the anti-corrosion, nano-black passivation type metal material is made of stainless steel powder, the surface-modified tungsten carbide in Preparation Example 3, and the spherical graphene-modified stainless steel powder in Preparation Example 6 through a powder metallurgy process.

[0097] The difference between Example 3 and Example 1 is that the anti-corrosion, nano-black passivation type metal material is made of stainless steel powder, the surface-modified tungsten carbide in Preparation Example 4, and the spherical graphene-modified stainless steel powder in Preparation Example 6 through a powder metallurgy process.

[0098] The difference between Example 4 and Example 1 is that the anti-corrosion, nano-black passivation type metal material is made of stainless steel powder, the surface-modified tungsten carbide in Preparation Example 2, and the spherical graphene-modified stainless steel powder in Preparation Example 7 through a powder metallurgy process.

[0099] The difference between Example 5 and Example 1 is that the anti-corrosion, nano-black passivation type metal material is made of stainless steel powder, the surface-modified tungsten carbide in Preparation Example 2, and the spherical graphene-modified stainless steel powder in Preparation Example 8 through a powder metallurgy process.

[0100] The difference between Example 6 and Example 1 is that the anti-corrosion, nano-black passivation type metal material is made of stainless steel powder, the surface-modified tungsten carbide in Preparation Example 2, and the spherical graphene-modified stainless steel powder in Preparation Example 10 through a powder metallurgy process.

[0101] The difference between Example 7 and Example 1 is that the anti-corrosion, nano-black passivation type metal material is made of stainless steel powder, the surface-modified tungsten carbide in Preparation Example 2, and the spherical graphene-modified stainless steel powder in Preparation Example 11 through a powder metallurgy process.

[0102] The difference between Example 8 and Example 1 is that the anti-corrosion, nano-black passivation type metal material is made of stainless steel powder, the surface-modified tungsten carbide in Preparation Example 2, and the spherical graphene-modified stainless steel powder in Preparation Example 12 through a powder metallurgy process.

[0103] The difference between Example 9 and Example 1 is that the total mass of the surface-modified tungsten carbide and spherical graphene-modified stainless steel powder is equal to 0.75wt% of the mass of the anti-corrosion, nano-black passivation type metal material.

[0104] The difference between Example 10 and Example 1 is that the total mass of the surface-modified tungsten carbide and spherical graphene-modified stainless steel powder is equal to 1.0wt% of the mass of the anti-corrosion, nano-black passivation type metal material.

[0105] The difference between Example 11 and Example 1 is that the mass ratio of the surface-modified tungsten carbide to the spherical graphene-modified stainless steel powder is 2:1.

[0106] The difference between Example 12 and Example 1 is that the mass ratio of the surface-modified tungsten carbide to the spherical graphene-modified stainless steel powder is 3:2.

[0107] The difference between Example 13 and Example 1 is that the mass ratio of the surface-modified tungsten carbide to the spherical graphene-modified stainless steel powder is 1:1.

[0108] The difference between Example 14 and Example 1 is that the mass ratio of the surface-modified tungsten carbide to the spherical graphene-modified stainless steel powder is 1:2.

[0109] The difference between Example 15 and Example 1 is that the mass ratio of the surface-modified tungsten carbide to the spherical graphene-modified stainless steel powder is 1:5.

[0110] The difference between Example 16 and Example 1 is that the anti-corrosion, nano-black passivation type metal material is made of stainless steel powder, the surface-modified tungsten carbide in Preparation Example 3, and the spherical graphene-modified stainless steel powder in Preparation Example 11 through a powder metallurgy process. The total mass of the surface-modified tungsten carbide and the spherical graphene-modified stainless steel powder is equal to 0.75wt% of the mass of the anti-corrosion, nano-black passivation type metal material. The mass ratio of the surface-modified tungsten carbide to the spherical graphene-modified stainless steel powder is 3:2.

[0111] The difference between Example 17 and Example 1 is that in step three, the mixed alloy powder obtained in step two is placed in a molding mold for hot isostatic pressing treatment, and the hot isostatic pressing parameters are as follows: molding temperature 880-950°C, molding pressure: first pressurize to 150MPa at 20MPa / s, hold pressure for 15s, then pressurize to 200MPa at 10MPa / s, hold pressure for 25s, then pressurize to 350MPa at 5MPa / s, hold pressure for 30s, then pressurize to 500MPa at 1MPa / s, hold pressure for 30s, then pressurize to 600MPa at 0.5MPa / s, hold pressure for 60s, then reduce the pressure to 300MPa at 1MPa / s, hold pressure for 60s, then reduce the pressure to 200MPa at 5MPa / s, hold pressure for 30s, finally reduce the pressure to 0MPa at 20MPa / s, the molding speed is 1mm / s, cool to room temperature, and grind off burrs to obtain a semi-finished product.

[0112] The difference between Example 18 and Example 16 is that: in step 3, the mixed alloy powder obtained in step 2 is placed in a molding die for hot isostatic pressing, and the hot isostatic pressing parameters are as follows: molding temperature 880-950°C, molding pressure: first pressurize to 150MPa at 20MPa / s, hold pressure for 15s, then pressurize to 200MPa at 10MPa / s, hold pressure for 25s, then pressurize to 350MPa at 5MPa / s, hold pressure for 30 s, then pressurize to 500MPa at 1MPa / s, hold the pressure for 30s, then pressurize to 600MPa at 0.5MPa / s, hold the pressure for 60s, then reduce the pressure to 300MPa at 1MPa / s, hold the pressure for 60s, then reduce the pressure to 200MPa at 5MPa / s, hold the pressure for 30s, finally reduce the pressure to 0MPa at 20MPa / s, the molding speed is 1mm / s, cool to room temperature, grind off the burrs to get the semi-finished product.

[0113] The difference between Comparative Example 1 and Example 1 is that the anti-corrosion, nano-black passivation type metal material is made of stainless steel powder, nano-tungsten carbide and graphene through a powder metallurgy process.

[0114] The content of nano-tungsten carbide in the anti-corrosion, nano-black passivation type metal material prepared in Comparative Example 1 is equal to the mass of the surface-modified tungsten carbide in the anti-corrosion, nano-black passivation type metal material prepared in Example 1.

[0115] The graphene content in the anti-corrosion, nano-black passivation type metal material prepared in Comparative Example 1 is equal to the mass of the surface-modified graphene in the anti-corrosion, nano-black passivation type metal material prepared in Example 1.

[0116] The difference between Comparative Example 2 and Example 1 is that the anti-corrosion, nano-black passivation type metal material is made of stainless steel powder, the surface-modified tungsten carbide in Preparation Example 2, and graphene through a powder metallurgy process.

[0117] The graphene content in the anti-corrosion, nano-black passivation type metal material prepared in Comparative Example 2 is equal to the mass of the surface-modified graphene in the anti-corrosion, nano-black passivation type metal material prepared in Example 1.

[0118] The difference between Comparative Example 3 and Example 1 is that the anti-corrosion, nano-black passivation type metal material is made of stainless steel powder, nano-tungsten carbide, and the surface-modified graphene in Preparation Example 6 through a powder metallurgy process.

[0119] The content of nano-tungsten carbide in the anti-corrosion, nano-black passivation type metal material prepared in Comparative Example 3 is equal to the mass of the surface-modified tungsten carbide in the anti-corrosion, nano-black passivation type metal material prepared in Example 1.

[0120] The difference between Comparative Example 4 and Example 1 is that the anti-corrosion, nano-black passivation type metal material is made of stainless steel powder, the surface-modified tungsten carbide in Preparation Example 1, and the spherical graphene-modified stainless steel powder in Preparation Example 6 through a powder metallurgy process.

[0121] The difference between Comparative Example 5 and Example 1 is that the anti-corrosion, nano-black passivation type metal material is made of stainless steel powder, the surface-modified tungsten carbide in Preparation Example 1, and the spherical graphene-modified stainless steel powder in Preparation Example 5 through a powder metallurgy process.

[0122] The difference between Comparative Example 6 and Example 1 is that the anti-corrosion, nano-black passivation type metal material is made of stainless steel powder, the surface-modified tungsten carbide in Preparation Example 2, and the spherical graphene-modified stainless steel powder in Preparation Example 5 through a powder metallurgy process.

[0123] The difference between Comparative Example 7 and Example 1 is that the anti-corrosion, nano-black passivation type metal material is made of stainless steel powder, the surface-modified tungsten carbide in Preparation Example 2, and the spherical graphene-modified stainless steel powder in Preparation Example 9 through a powder metallurgy process.

[0124] The difference between Comparative Example 8 and Example 1 is that the anti-corrosion, nano-black passivation type metal material is made of stainless steel powder and the surface-modified tungsten carbide in Preparation Example 2 through a powder metallurgy process. The amount of surface-modified tungsten carbide added in Preparation Example 2 is 0.5 wt%.

[0125] The difference between Comparative Example 9 and Example 1 is that the anti-corrosion, nano-black passivation type metal material is made of stainless steel powder and the spherical graphene-modified stainless steel powder in Preparation Example 6 by powder metallurgy. The addition amount of the spherical graphene-modified stainless steel powder in Preparation Example 6 is 0.5wt%.

[0126] The difference between Comparative Example 10 and Example 1 is that the total mass of the surface-modified tungsten carbide and the spherical graphene-modified stainless steel powder is equal to 0.2 wt % of the mass of the anti-corrosion, nano-black passivation type metal material.

[0127] The difference between Comparative Example 11 and Example 1 is that the total mass of the surface-modified tungsten carbide and spherical graphene-modified stainless steel powder is equal to 1.5wt% of the mass of the anti-corrosion, nano-black passivation type metal material.

[0128] The difference between Comparative Example 12 and Example 1 is that in step three, the mixed alloy powder obtained in step two is placed in a molding mold for hot isostatic pressing, and the hot isostatic pressing parameters are as follows: molding temperature 920°C, molding pressure: first pressurize to 600MPa at 15MPa / s, maintain pressure for 170s, and then reduce pressure to 0MPa at 20MPa / s, the molding speed is 1.0mm / s, cool to room temperature, and grind off burrs to obtain a semi-finished product.

[0129] The difference between Comparative Example 13 and Example 1 is that: in step 4, the semi-finished product obtained in step 3 is quenched by heating to 460°C at 5°C / min and keeping it for 15min, adjusting the temperature to 1020°C at 10°C / min and keeping it for 90min, and then gas quenching is performed: a nitrogen-oxygen mixed gas with a temperature of 65°C is input, and the oxygen volume content in the nitrogen-oxygen mixed gas is 15%, and the temperature is quickly reduced to 400°C, and then tempering is performed: the temperature is adjusted to 650°C at 5°C / min. ℃, keep warm for 1.5h, then cool down to 220℃ at 10℃ / min, open the furnace and cool naturally, secondary tempering treatment: adjust the temperature to 680℃ at 6℃ / min, keep warm for 1.5h, then cool down to 200℃ at 15℃ / min, open the furnace and cool naturally to room temperature to obtain anti-corrosion metal material, the anti-corrosion metal material is coated with 20μm thick nano passivation coating by roller coating, and baked at 175℃ until dry to obtain the finished anti-corrosion, nano black passivation metal material.

[0130] Performance test: 1. Salt spray resistance test method: Determined in accordance with GB / T 2518-2008. 2. Hardness test method: Determined in accordance with GB / T230.1-2004 "Metallic Rockwell Hardness Test Part 1: Test Method". 3. Yield strength test: Determined in accordance with national standard GB / T232-2010. 4. Toughness test is V-impact test: Determined in accordance with national standard GB / T 229-2007.

[0131] Table 1: Test parameter table of anti-corrosion and nano-black passivation metal materials prepared in Examples 1-18 and Comparative Examples 1-13

[0132]

[0133]

[0134] It can be seen from Example 1 and Comparative Examples 1-3 and Table 1 that the anti-corrosion, nano-black passivation metal material made from stainless steel powder, surface-modified tungsten carbide, and spherical graphene-modified stainless steel powder by powder metallurgy has good corrosion resistance, wear resistance, and mechanical strength. Without surface modification of tungsten carbide and graphene, their dispersion performance in the stainless steel matrix is ​​biased, resulting in a deviation in the mechanical strength of the prepared steel, which cannot meet the actual use requirements of internal metal parts of electronic products.

[0135] It can be seen from Examples 1-8 and Comparative Examples 4-9 and Table 1 that the loading rate of nano-modified iron metal particles in the surface-modified tungsten carbide is ≥5wt%. Otherwise, the dispersion performance of the prepared surface-modified tungsten carbide in the stainless steel matrix is ​​relatively poor, resulting in low mechanical strength of the prepared steel, limiting its scope of application.

[0136] It can be seen from Examples 1-8 and Comparative Examples 4-9 and Table 1 that the loading rate of nano-modified iron metal particles in the surface-modified graphene is ≥5wt%. Otherwise, the dispersion performance of the prepared surface-modified graphene in the stainless steel matrix is ​​relatively poor, resulting in low mechanical strength of the prepared steel, limiting its scope of application.

[0137] It can be seen from Examples 1-8 and Comparative Examples 4-9 and Table 1 that the metallic iron single atom loading rate in the surface single-atom iron-modified graphene is ≥1wt%. Otherwise, the dispersion performance of the prepared surface-modified graphene in the stainless steel matrix is ​​relatively poor, resulting in low mechanical strength of the prepared steel, limiting its scope of application.

[0138] It can be seen from Example 1, Examples 9-10 and Comparative Examples 10-11 and Table 1 that the total mass of the surface-modified tungsten carbide and spherical graphene-modified stainless steel powder is equal to 0.75wt% of the mass of the anti-corrosion, nano-black passivated metal material, and the prepared steel has better comprehensive performance and better economic performance.

[0139] In combination with Example 1, Examples 11-15 and Comparative Examples 8-9 and Table 1, it can be seen that the surface-modified tungsten carbide and the spherical graphene-modified stainless steel powder are compounded and used to prepare the steel with better comprehensive performance and better economic performance. The mass ratio of the surface-modified tungsten carbide to the spherical graphene-modified stainless steel powder is preferably 3:2. The corrosion resistance, wear resistance and mechanical strength of the prepared steel are relatively good and the production economy is more economical, which is suitable for industrial mass production.

[0140] It can be seen from Example 1, Example 17 and Comparative Example 12 and Table 1 that the anti-corrosion, nano-black passivation type metal material prepared by the preparation method provided in the present invention has good corrosion resistance, wear resistance and mechanical strength, and different hot isostatic pressing processes have a direct impact on the comprehensive performance of the prepared anti-corrosion, nano-black passivation type metal material.

[0141] It can be seen from Example 1 and Comparative Example 13 and Table 1 that the corrosion-resistant, nano-black passivated metal material prepared by the preparation method provided in the present invention has good corrosion resistance, wear resistance and mechanical strength, and the high-energy laser melting treatment especially improves the corrosion resistance and wear resistance of the steel.

[0142] In summary, the anti-corrosion, nano-black passivated metal material of the present invention meets the salt spray resistance of steel in the electronics industry and does not require subsequent electroplating treatment. The precision of electronic devices is relatively good, the product yield is improved, and the product cost is reduced.

[0143] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. An anti-corrosion, nano-black passivated metal material, characterized by: The anti-corrosion, nano-black passivation type metal material is made of stainless steel powder, surface-modified tungsten carbide, and spherical graphene-modified stainless steel powder through a powder metallurgy process; the total mass of the surface-modified tungsten carbide and the spherical graphene-modified stainless steel powder is equal to 0.5-1.0wt% of the mass of the anti-corrosion, nano-black passivation type metal material; the mass ratio of the surface-modified tungsten carbide to the spherical graphene-modified stainless steel powder is 1:(0.1-5); the surface-modified tungsten carbide includes a matrix tungsten carbide and nano-modified metal particles loaded on the surface of the matrix tungsten carbide, and the nano-modified metal particles at least include nano-iron particles.

2. The anti-corrosion, nano-black passivation metal material according to claim 1, characterized in that: The matrix tungsten carbide is nano tungsten carbide with an average particle size of 50-500nm; the nano modified metal particles are loaded on the surface of the matrix tungsten carbide by a sol-gel method, and the loading rate of the nano modified metal particles is ≥5wt%.

3. The anti-corrosion, nano-black passivation metal material according to claim 2, characterized in that: The spherical graphene modified stainless steel powder is prepared by a spraying method from stainless steel powder and surface modified graphene; the amount of the surface modified graphene added is equal to 5-10wt% of the mass of the spherical graphene modified stainless steel powder; the particle size D of the spherical graphene modified stainless steel powder is 50 ≤35 microns.

4. The anti-corrosion, nano-black passivation metal material according to claim 3, characterized in that: The surface modified graphene comprises a matrix graphene and nano-modified metal particles loaded on the surface of the matrix graphene, wherein the loading rate of the nano-modified metal particles is ≥5wt%; and the nano-modified metal particles at least comprise nano-iron particles.

5. The anti-corrosion, nano-black passivation metal material according to claim 3, characterized in that: The surface modified graphene includes a matrix graphene and metal single atoms anchored at defect sites of the matrix graphene, the metal single atom loading rate is ≥1wt%, and the metal single atoms include at least iron single atoms.

6. The anti-corrosion, nano-black passivation metal material according to claim 3, characterized in that: The preparation method of the spherical graphene modified stainless steel powder is as follows: S1. The stainless steel powder and the surface-modified graphene were mixed evenly and then transferred to a planetary ball mill, and tungsten carbide was used as grinding beads, and dry ball milling was performed at 60-80 rpm for 20-40 min to obtain a mixed alloy powder; S2. The mixed alloy powder obtained in S1 is used to prepare spherical alloy powder by aerosol method. The particle size of the obtained spherical alloy powder is D 50 5-35 microns, tap density ≥1.75g / cm 3 .

7. The anti-corrosion, nano-black passivation metal material according to claim 3, characterized in that: The total mass of the surface-modified tungsten carbide and spherical graphene-modified stainless steel powder is equal to 0.7-0.8wt% of the mass of the anti-corrosion, nano-black passivation type metal material; the mass ratio of the surface-modified tungsten carbide to the spherical graphene-modified stainless steel powder is 1:(0.5-2).

8. The anti-corrosion, nano-black passivation metal material according to claim 7, characterized in that: The total mass of the surface-modified tungsten carbide and spherical graphene-modified stainless steel powder is equal to 0.7-0.8wt% of the mass of the anti-corrosion, nano-black passivation type metal material; the mass ratio of the surface-modified tungsten carbide to the spherical graphene-modified stainless steel powder is 3:

2.

9. A process for preparing an anti-corrosion, nano black passivation metal material according to any one of claims 1 to 8, characterized in that: The following steps are involved: Step 1, preparation of surface-modified tungsten carbide and spherical graphene-modified stainless steel powder; Step 2: The surface-modified tungsten carbide and spherical graphene-modified stainless steel powder prepared in step 1 are mixed evenly with the stainless steel powder according to a ratio, and then transferred to a planetary ball mill, with tungsten carbide as a grinding bead, and dry-milled at 60-80 rpm for 5-15 minutes to obtain a mixed alloy powder; Step 3: The mixed alloy powder obtained in step 2 is placed in a molding die for hot isostatic pressing. The hot isostatic pressing parameters are as follows: molding temperature 880-950°C, molding pressure: first pressurize to 120-160MPa at 15-20MPa / s, hold pressure for 10-20s, then pressurize to 200-240MPa at 8-10MPa / s, hold pressure for 20-30s, then pressurize to 320-350MPa at 4-6MPa / s, hold pressure for 20-30s, and then pressurize to 4 at 1-2MPa / s. 50-500MPa, hold pressure for 30-60s, then pressurize to 550-600MPa at 0.5-1MPa / s, hold pressure for 30-60s, then reduce pressure to 280-320MPa at 1-2MPa / s, hold pressure for 30-60s, then reduce pressure to 160-200MPa at 4-8MPa / s, hold pressure for 30-60s, finally reduce pressure to 0MPa at 15-20MPa / s, molding speed is 0.5-5mm / s, cool to room temperature, grind burrs to get semi-finished products; Step 4: Perform high-energy laser melting treatment on the surface of the semi-finished product obtained in step 3, with a laser spot temperature of 2880-3000°C, a laser scanning speed of 400-1200mm / s, and a spot diameter of 0.04-0.08mm. After the high-energy laser melting treatment, perform quenching + tempering treatment to obtain an anti-corrosion metal material, and apply a nano passivation coating of 8-20μm thickness on the anti-corrosion metal material by roller coating, and bake at 150-250°C until completely dry to obtain a finished anti-corrosion, nano black passivation metal material; The nano passivation coating is made of nano passivation paint, which includes water-based polyester resin, silane coupling agent, carbon black, and black titanium dioxide nanoparticles. The total mass of carbon black and black titanium dioxide nanoparticles accounts for 3-10wt% of the total mass of the nano passivation paint; the mass of the silane coupling agent accounts for 0.5-1.0wt% of the total mass of the nano passivation paint; the solid content of the water-based polyester resin is 30-55wt%, and the mass of the polyurethane latex particles in the nano passivation paint accounts for 25-40wt% of the total mass of the nano passivation paint.

10. An anti-corrosion, nano-black passivated metal material according to any one of claims 1 to 8 used in internal metal parts of electronic products.

Citation Information

Patent Citations

  • Preparation method and application of aminated graphene

    CN105645392A

  • Water-based coating, preparing method thereof and using method of the coating

    CN105838173A

  • Method for preparing solid oxide fuel cell anode by two-dimensional material assisted impregnation method

    CN108550866A

  • Preparation method of metal monoatom-doped graphene

    CN110642245A

  • Stainless steel product and preparation method thereof

    CN113798498A

Cited By

  • PBT / PC composite material and preparation method and application thereof

    CN121045762A